KEBEBASAN MAHASISWA DALAM BERPENDAPAT DARI PRESPEKTIF HAM - Qudsya, Amalia Laila; Habibah, Siti Maizul (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
From a human rights standpoint, students' fundamental right to free speech is protected by the state constitution and fundamental laws. For students to be able to express their opinions without fear of retaliation or intimidation, they must have the fundamental right to freedom of expression. The state's basic laws and the constitution both safeguard the right to freedom of expression from the perspective of human rights. Of course, there are limitations on the right to free speech that must be observed, such as the requirement to respect the legal system and the human rights of others. The 1945 Constitution's Article 28E, paragraph (3), which states that "Every person shall have the right to freedom of association, assembly, and expression of opinion," ensures freedom of speech in Indonesia. The freedom of expression is regulated by Law Number 39 of 1999 Concerning Human Rights, which also safeguards the right to freedom of opinion and expression. However, in practice, speech freedom is often curtailed by a variety of factors, such as official pressure, intimidation, and threats of violence. Therefore, it is crucial to strengthen the defense of the right to free speech and increase public understanding of its importance